2015
DOI: 10.1186/s13567-015-0181-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the capability of the PCV2 genome to encode miRNAs: lack of viral miRNA expression in an experimental infection

Abstract: Porcine circovirus type 2 (PCV2) is a ssDNA virus causing PCV2-systemic disease (PCV2-SD), one of the most important diseases in swine. MicroRNAs (miRNAs) are a new class of small non-coding RNAs that regulate gene expression post-transcriptionally. Viral miRNAs have recently been described and the number of viral miRNAs has been increasing in the past few years. In this study, small RNA libraries were constructed from two tissues of subclinically PCV2 infected pigs to explore if PCV2 can encode viral miRNAs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In this study, we have found that ASFV, under these experimental conditions, does not express viral miRNAs like other viruses such as Cowpox virus or Porcine circovirus type 2 (PCV2) [ 34 , 35 ]. Interestingly, in a recent and exhaustive work carried out by Jaing et al about gene expression in blood of ASFV-infected pigs, wherein some DE host miRNA have been identified, viral miRNAs are not described [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have found that ASFV, under these experimental conditions, does not express viral miRNAs like other viruses such as Cowpox virus or Porcine circovirus type 2 (PCV2) [ 34 , 35 ]. Interestingly, in a recent and exhaustive work carried out by Jaing et al about gene expression in blood of ASFV-infected pigs, wherein some DE host miRNA have been identified, viral miRNAs are not described [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, viral miRNAs were also reported to participate in viral or host cellular gene expression [80]. However, the PCV2 genome does not encode any known miRNAs that are expressed in vivo during subclinical infection [81].…”
Section: Cellular Micrornas Involved In Pcv2 Infectionmentioning
confidence: 96%
“…The altered expression of cellular miRNAs may facilitate and/or restrict viral replication by deregulating their target genes after viral infections [13]. No miRNAs encoded by PCV2 genomic DNA were detected in tonsil and mediastinal lymph node tissues from PCV2-infected pigs [14], hence, PCV2 may completely invade and colonize other life processes by regulating host miRNAs. The miRNA expression pattern in PCV2 of sub-clinically infected pigs, non-infected pigs, and PK-15 cells expressing each of the three PCV2-encoded open reading frames (ORFs) have been reported [15,16,17].…”
Section: Introductionmentioning
confidence: 99%